Peranan Lebah Trigona laeviceps (Hymenoptera: Apidae) dalam Produksi Biji Kailan (Brassica oleracea var. alboglabra) - Wulandari, Anggreny Pramitha; Atmowidi, Tri; Kahono, dan Sih (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Kale (Brassica oleraceae) has small and compound floral-type and usually visited by bees, including Trigona laeviceps (Apidae: Melliponini) as pollinator which can increase fruit and seed production of many species of agricultural crops. Aims of the research were to study foraging activity and the role of T. laeviceps in seed production of kale. Three treatments were used i.e., caged crop with one colonies of T. laeviceps, open crop with one colonies of T. laeviceps and caged crop without bee. Foraging activities of T. laeviceps were observed during the flowering by using a focal sampling method and visual method. Measuring the amount of pollen was done by using glycerol and alcohol (70%) with a ratio 4:1 and pollen viability was observed in Brewbaker and Kwack solutions. Result showed that flower handling time of T. laeviceps was highest during 09.00-10.00 (36.3 seconds/flower) with foraging rate was 8.26 flowers per 5 minutes. Flower handling time was lowest during 15.00-16.00 (10.6 seconds/flower) with foraging rate was 28.6 flowers per 5 minutes. Pollen load of T. laeviceps in the caged crop (8125 grain) was higher than in open crop (3000 grain). Viability of the pollen in the caged crop (80.8%) was higher than that of open crop (31.4%). Pollination by T. laeviceps increased 141% number of pods per plant, 48% number of seeds per pod, 204% of seed weight per plant, and 177% of seed germination. Keywords: foraging activity, pollination, fruit set, pollen viability